Respuesta :

Answer:

6 2/3

Explanation:

Given the expression:

[tex]\lbrack6-\mleft(-9\mright)\rbrack\div\frac{-9}{-4}[/tex]

First, we simplify to obtain:

[tex]=\lbrack6+9\rbrack\div-\frac{9}{-4}[/tex]

Note that -9/-4=9/4. The minus sign cancels each other out.

This gives us:

[tex]15\div\frac{9}{4}[/tex]

We then change the division sign to multiplication as shown below:

[tex]\begin{gathered} =15\times\frac{4}{9} \\ =\frac{60}{9} \\ =6\frac{6}{9} \\ =6\frac{2}{3} \end{gathered}[/tex]

ACCESS MORE